Exposure to excessive sounds during orchestra rehearsals and temporary hearing changes in hearing among musicians - Adam Dudarewicz; Małgorzata Pawlaczyk-Łuszczyńska; Małgorzata Zamojska-Daniszewska; Kamil Zaborowski (Nofer Institute of Occupational Medicine, 2015)
Background: It has been shown that musicians are at risk of noise-induced hearing loss. The aim of the study has been to evaluate the temporary changes of hearing in the case of orchestral musicians after group rehearsals. Material and Methods: The study group comprised 18 orchestral musicians, aged 30-58 years old (mean: 40 years old) having 12-40 years (mean: 22 years) of professional experience. The temporary changes in hearing after group rehearsals were determined using transient-evoked otoacoustic emissions (TEOAEs). Noise exposures during group rehearsals were also evaluated. Results: Musicians' hearing threshold levels were higher (worse) than expected for the equivalent non-noise-exposed population. Moreover, the high frequency notched audiograms were observed in some of them. After rehearsals, during which musicians were exposed to orchestral noise at A-weighted equivalent-continuous sound pressure level (normalized to 8-h working day) varied from 75.6-83.1 dB (mean: 79.4 dB). The significant post-exposure reductions of TEOAE amplitudes (approx. 0.7 dB) both for the total response and frequency bands of 2000 and 3000 Hz were noted. However, there were no significant differences between pre- and postexposure reproducibility of TEOAE. Conclusions: Obtained results have confirmed that orchestral musicians are at risk of hearing loss due to their professional activities, even at exposures to orchestral noise less than the limit values for occupational noise. Med Pr 2015;66(4):479-486